GC-MS validation of the organic ionic impurity tetra-n-butylammonium bromide in Teneligliptin - Murugan Maniavannan, Paramasivam Parthiban,, Palaniappan Ilayaraja, Jagatheesan Rathinavel (Journal of Applied Pharmaceutical Science, 2023)
Teneligliptin is a potential drug to control type 2 diabetes but during the synthesis of Teneligliptin, the tetra-n-butylammonium bromide (TBAB) is used as a phase transfer catalyst, and thus it reaches the drug as an impurity. The existing analytical methods for the determination of TBAB in drugs are very limited, particularly with no effective GC method. Thus, the new method developed and optimized on Agilent 5977B GC/MSD equipped with DB-1 capillary column (60 m × 0.32 mm × 0.25 μm) using helium as carrier gas. Detection was performed at the m/z of 100, 142, and 185 using selective ion monitoring mode. The concentration range of 1.0–1,500 ppm with a correlation coefficient of 0.9971 was determined by the linearity curve. The detection (LOD) and quantitation limits (LOQ) of TBAB were 0.3 and 1.0 μg/g concerning the sample weight. The average recovery of TBAB was 97.8%, indicating the method is accurate, and the RSD area of the six replicates injection of TBAB standard was